A simple single jar "on–off fluorescence" designed system for the determination of mitoxantrone using an eosin Y dye in raw powder, vial, and human biofluids. Issue 12 (7th March 2022) - Hamad, Ahmed Abdulhafez; Ali, Ramadan; Derayea, Sayed M.
Abstract : This work describes a green fluorescence on–off system that relies on establishing a simple ion association complex pairing the mitoxantrone antineoplastic drug with the eosin Y reagent in a slightly acidic solution. Abstract : In this work, a direct, simple, one-pot, and green spectrofluorimetric approach was applied to measure mitoxantrone, a chemotherapeutic agent, through a green validated method. The suggested approach focused on establishing an easy association complex combining mitoxantrone and the eosin Y reagent in a slightly acidic solution. The fluorometric analysis was dependent on off-mitoxantrone action on the emission intensity of the dye (eosin Y) at 544.5 nm (excitation = 301 nm). The devised system has a linear range of 0.07–2.5 μg mL −1 and a detection limit of 0.016 μg mL −1 . All system parameters for the formation of mitoxantrone–eosin Y complexes were modulated analytically. Also, the system was reviewed in agreement with ICH criteria. Furthermore, the proposed model was approached to quantify mitoxantrone in its pharmaceutical vial dosage form with high recoveries. Also, the proposed spectroscopic design was efficiently employed to detect the investigated drug in body fluids (blood and urine). Lastly, the designed method was evaluated from a greenness point of view according to eco-scale.